Application of GIS on the determination analysis of sustainable food agricultural land in Serang Regency - Safariah, Rifiati; Kurniadie, Denny (2015)
The rapid conversion of agricultural land into non agricultural land directly reduce the land availability for food production activity. Therefore, to control the rate of food agricultural land conversion needs many efforts, such as implementing sustainable food agricultural land program.This study aimed to analyze the determination of sustainable food agricultural land in Serang Regency.By using GIS technology and doing weighted overlay analysis, the result of the research showed that based on optimistic scenario, the determination of sustainable food agricultural land covered 21.489,30 Ha of rice field. While based on pessimistic scenario, the determination of sustainable food agricultural land covered 37.176,25 Ha of rice field. The determination of sustainable food agricultural land needs to be carried out in order to ensure the sustainability of the food supply and to protect the fertile lands which have high productivity in Serang Regency.